Dispersed SnO2 nanoparticles on MoS2 nanosheets for superior gas-sensing performances to ethanol1. Issue 97 (21st October 2015) - Yan, Huihui; Song, Peng; Zhang, Su; Yang, Zhongxi; Wang, Qi
<x xml:space="preserve">Abstract</x> Novel composites with superior gas-sensing performance were successfully obtained by dispersing SnO2 nanoparticles on the surfaces of MoS2 nanosheets.